Coding all-in-one - Minnick, Chris; Abraham, Nikhil; Burd, Barry; Holland, Eva; Massaron, Luca; Mueller, John 1958- (John Wiley & Sons, Inc., 2022)
Adding some coding know-how to your skills can help launch a new career or bolster an old one. Coding All-in-One For Dummies offers an ideal starting place for learning the languages that make technology go. This edition gets you started with a helpful explanation of how coding works and how it's applied in the real-world before setting you on a path toward writing code for web building, mobile application development, and data analysis. Add coding to your skillset for your existing career, or begin the exciting transition into life as a professional developer-Dummies makes it easy. This book serves up insight on the basics of coding, designed to be easy to follow, even if you've never written a line of code in your life. You can do this.
Description based on print version record
Keywords: Computer programming; Coding theory; Programmation (Informatique); computer programming